Cenários formativos da docência transdisciplinar em ambientes virtuais de aprendizagem - Machado, Michelle Jordão (2014)
This paper, named Cenários Formativos da Docência Trandisciplinar em AVA [Formative Landscape of Transdisciplinary Teaching in VLE], appears to search for knowing and reorganizing the life histories and academics’ personal, professional and intellectual formative itineraries learning from conversation about the following main matter: Which itineraries professors who work in virtual environment of learning built in their metaformative processes? What these itineraries showed about conceptions, features, attitudes, projects, potential and limits of teaching in virtual learning environments? Arranging research trouble, other issues appear as source or development of initial question: what feature pedagogical practices in virtual learning environment in transdisciplinary perspective? How far this practice in virtual learning environment – VLE – offers (re)construction of pedagogic arrays of professors? How digital interfaces presented in VLE are constituted as boosting of formative landscapes, according to transdisciplinary principles? Within this context, the goal of this research was to investigate conceptions, features, attitudes, projects, transformation, potential and limits of professor in VLE which aims development of student metaformative processes, based on transdisciplinarity principles, with expectation of understanding and answering to presented issues. The research was developed in qualitative feature. The corpus of this study was generated by narration of formative itinerary from six undergraduate professors, considered by their managers as holders of transdisciplinary attitudes in VLE. These narrations measured, in the first moment of research, the different steps of life, main experiences as students, from basic education to Post-graduation, the teaching and the projects in college education. In the second moment, the professors described the constitution of formative landscapes of transdisciplinary teaching in college education in VLE: professor’ crucial periodization and moments, professor’s attitudes, addition of new educational practice from experience with digital interfaces, educational measurement and teaching strategies, from teaching and evaluation. These conceptions were articulated by professor, who offered: to understand that itineraries are types of proofs covered by sense and meaning of pedagogical arrays, to find heterogeneous features that, sometimes, can be normal, from motivation, needs, attitudes and desire of being and come-to-be in university teaching, to reveal models and principles which manage professors’ educational speeches, the place to include professor feeling, thinking and working, to know perceptions of transformation moments occurred in the process, and to immerse in singularities of self-knowledge, tracer, and of six professors researched. The experiences, conceptions and practices of professors pointed a transdisciplinary teaching in formative landscapes implicated by ethical attitude, consideration of pedagogical arrays, from multi-temporality of learning, science articulated to consciousness, possibility of access, flexibility, uncertainty, emergency in moments of pedagogical measurement, logical third-person included, consideration of multidimensionality of human being, from independence, autopoiesis, self-organization, metacognition and metatransformation, from transculturalism and transreligiosity.